TELAâAH KONSEP THE TAO OF ISLAM - Muhazir, Muhazir (At-Tafkir, 2017)
Sachiko Murata has given a new scientific discourse in Islamic studies, especially in gender chess with a feminine approach that seeks to explain the relationship of cosmoslogi with humankind, in his study, Sachiko also combine it with the Chinese scholarship Tao with Tao of Islam collaboration mengahasilkan new treasures by taking the opinion- Sufis, Sachiko rate that to understand the relationship of the difference is required understanding of Sufis with background wisdom in understanding the cosmos and the creation of god. Sachikos anxiety begins when he takes on the task of teaching his students in America about Islamic studies, many of which are felt by Sachiko in his teaching, where students ask about the oppression of women in the east and students departing from the negative doctrinal values of womens oppression Islam.